Architectural design of IoT-based healthcare applications - Barroca Filho, Itamir de Morais (2019)
The myriad of connected things promoted by the Internet of Things (IoT) and the data captured by them is making possible the development of applications in various markets, such as transportation, buildings, energy, home, industrial and healthcare. Concerning the healthcare market, it is expected the development of these applications as part of the future, since it can improve e-Health to allow hospitals to operate more efficiently and patients to receive better treatment. The IoT can be the main enabler for distributed healthcare applications, thus having a significant potential to contribute to the overall decrease of healthcare costs while increasing the health outcomes. However, there are a lot of challenges in the development and deployment of this kind of application, such as interoperability, availability, performance, and security. The complex and heterogeneous nature of IoT-based healthcare applications makes its design, development and deployment difficult. It also causes an increase in the development cost, as well as an interoperability problem with the existing systems. To contribute to solve the aforementioned challenges, this thesis aims at improving the understanding and systematization of the IoT-based healthcare applications’ architectural design. It proposes a software reference architecture, named Reference Architecture for IoT-based Healthcare Applications (RAH), to systematically organize the main elements of these applications, its responsibilities and interactions, promoting a common understanding of these applications’ architecture. To establish RAH, a systematic mapping study of existing publications regarding IoT-based healthcare applications was performed, as well the study about quality attributes, tactics, architectural pattern and styles used in software engineering. As a result, RAH presents domain knowledge and software architectural solutions (i.e., architectural patterns and tactics) documented using architectural views. To assess RAH, a case study was performed by instantiating it to design the software architecture of a computational platform based on the Internet of Things (IoT) infrastructure to allow the intelligent remote monitoring of the patient’s health data (biometrics). With this platform, the clinical staff can be alerted of the health events that require immediate intervention and then prevent unwanted complications. Results evidenced that RAH is a viable reference architecture to guide the development of secure, interoperable, available, and efficient IoT-based healthcare applications, bringing contributions for the areas of e-Health and software architecture.